THE EXISTENCE OF BEJI PURA HYANG TIBHA AS A WELLNESS TOURISM ATTRACTION IN BANJAR BLAHTANAH, BATUAN KALER, SUKAWATI DISTRICT, GIANYAR REGENCY - Anak Agung Ari Sutraningsih; I Nyoman Subagia; I Ketut Wardana Yasa (Ride: Journal of Cultural Tourism and Religious Studies, 2024)
Excistences is a term that is often used to refer to the existence or existence of something in a philosophical, scientific or general context. The existence of a tourist attraction is seen from the management of the tourist area itself as well as the historical value contained in the tourist attraction. The existence of tourist attractions plays a vital role in preserving the cultural identity of a community, both for local residents and visitors from outside. The existence of Beji Pura Hyang Tibha as a wellness tourism attraction in Banjar Blahtanah Batuan Kaler, Sukawati District, Gianyar Regency is one of the health tourism sites which is one of the tourism potentials in pioneering tourism villages whose existence is known by many groups. This tourist attraction is not only famous for its cultural heritage but also for the presence of Beji, a place to do healing for cleansing the body and soul and peace of mind. There are four theories used in this research, namely; 1) Existence theory, 2)Tourist motivation theory, 3) Tourism management theory, and 4) Structural functional theory. This research is qualitative descriptive research using literature approaches in the fields of theology and cultural tourism, field observation and documentation. This research examines the problem of the existence of Beji Pura Hyang Tibha as a wellness tourism attraction, how it is managed and the influence of the physical environment on postmodern society in Banjar Blahtanah Batuan Kaler, Sukawati District, Gianyar Regency. The involvement of local communities (community-based tourism) and the use of current technology in managing health tourism attractions are supporting models for its management. The influence on the surrounding community where the Melukat wellness tourism attraction is located will indirectly have influences in terms of the economy, physical environment, socio-culture related to the existence of the tourist area as well as the influence of fitness on medical activities